A simple PCR-based quick detection of the economically important oriental fruit fly, Bactrocera dorsalis (Hendel) from India - Arya, Varun; Narayana, Srinivasa; Sinha, Twinke; Kandan, Aravindaram; Satyanarayana Raju, Samantapudi Venkata (Frontiers in Plant Science, 2024)
The oriental fruit fly, Bactrocera dorsalis (Hendel), is a significant economic and quarantine pest due to its polyphagous nature. The accurate identification of B. dorsalis is challenging at the egg, maggot, and pupal stages, due to lack of distinct morphological characters and its similarity to other fruit flies. Adult identification requires specialized taxonomist. Existing identification methods are laborious laborious, time consuming, and expensive. Rapid and precise identification is crucial for timely management. By analyzing variations in the mitochondrial cytochrome oxidase-1 DNA barcoding gene sequence, we developed a PCR-based assay using a species-specific primer (SSP), DorFP1/DorRP1, for accurate identification of B. dorsalis. The optimal annealing temperature for the SSP was determined to be 66℃, with no cross-amplification or primer-dimer formation observed. The SSP was validated with B. dorsalis specimens from various locations in northern and eastern India and tested for cross-specificity with six other economically significant fruit fly species in India. The primer specificity was further confirmed by the analysis of critical threshold (Ct) value from a qPCR assay. Sensitivity analysis showed the primer could detect template DNA concentrations as low as 1 pg/µl, though sensitivity decreased at lower concentrations. Sequencing of the SSPamplified product revealed over >99% similarity with existing B. dorsalis sequences in the NCBI GenBank. The developed SSP reliably identifies B. dorsalis across all developmental stages and sexes. This assay is expected to significantly impact pest identification, phytosanitary measures, and eradication programs for B. dorsalis.